A NOTE ON THE DISTRIBUTION AND HABITAT PREFERENCE OF Cyclotus longipilus VON MARTENS, 1865 FROM THE MAROS KARST AREA OF SOUTH SULAWESI (GASTROPODA: CYCLOPHORIDAE) - Marwoto , Ristiyanti M. (Treubia, 2013)
-